2004
DOI: 10.1073/pnas.0306660101
|View full text |Cite
|
Sign up to set email alerts
|

Attractant binding alters arrangement of chemoreceptor dimers within its cluster at a cell pole

Abstract: Many sensory systems involve multiple steps of signal amplification to produce a significant response. One such mechanism may be the clustering of transmembrane receptors. In bacterial chemotaxis, where a stoichiometric His-Asp phosphorelay from the kinase CheA to the response regulator CheY plays a central role, the chemoreceptors (methyl-accepting chemotaxis proteins) cluster together with CheA and the adaptor CheW, at a pole of a rodshaped cell. This clustering led to a proposal that signal amplification oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 54 publications
9
63
0
Order By: Relevance
“…Previously reported in vivo cross-linking studies are consistent with the clusters of dimers that are seen in the lzTar C WA complexes (16,17), and EM analyses of cell sections have shown evidence of membrane folds at the cell poles that could support the type of receptor signaling domain-to-signaling domain juxtaposition seen in our soluble receptor͞signaling complexes (32). Given that the sequences of the receptor cytoplasmic domains, CheA, and CheW are highly conserved in virtually all chemotactic prokaryotes, it seems that this organization of the receptor complexes, a tight complex with two sets of signaling domains oriented toward one another, could reflect the structure of active receptor͞CheW͞CheA complexes in vivo.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Previously reported in vivo cross-linking studies are consistent with the clusters of dimers that are seen in the lzTar C WA complexes (16,17), and EM analyses of cell sections have shown evidence of membrane folds at the cell poles that could support the type of receptor signaling domain-to-signaling domain juxtaposition seen in our soluble receptor͞signaling complexes (32). Given that the sequences of the receptor cytoplasmic domains, CheA, and CheW are highly conserved in virtually all chemotactic prokaryotes, it seems that this organization of the receptor complexes, a tight complex with two sets of signaling domains oriented toward one another, could reflect the structure of active receptor͞CheW͞CheA complexes in vivo.…”
Section: Discussionsupporting
confidence: 69%
“…Crosslinking studies of Tar and Tsr in membranes are consistent with a dimeric organization, although recent results indicate that higher order assemblies are probably involved (14)(15)(16)(17). Immuno-EM, immunofluorescence, and GFP-tagging studies have established that, within a cell, receptors, CheA, and CheW cluster together into large complexes that may contain thousands of subunits of each protein (18,19).…”
mentioning
confidence: 85%
“…This effective signaling indicated that the fundamental conformational change of ligand-induced transmembrane signaling required no greater structural complexity than the homodimer. This conclusion implies that changes in trimer or higher order interactions that have been observed or postu- lated to be related to signaling (21)(22)(23)(24) are not necessary for coupling of ligand occupancy in the periplasmic domain to conformational change in the cytoplasmic domain. The notion of transmembrane signaling occurring within the structure of single dimers is consistent with the large body of data that identifies the conformational change of transmembrane signaling in the periplasmic and transmembrane domains as the piston sliding of a single signaling helix of a ligand-occupied receptor dimer (3,25).…”
Section: Different Dependencies On Oligomeric State For Adaptational mentioning
confidence: 64%
“…Kim et al (27) have proposed a model of the receptor network in which the periplasmic domains of neighboring trimerbased receptor-signaling teams contact one another. Those interactions could account for the crosslinking results of Homma et al (26).…”
Section: Detection Of Receptor Trimers Of Dimers In Vivomentioning
confidence: 99%
“…Homma et al (26) recently described a crosslinking study of Tar with a cysteine reporter in the periplasmic, ligand-binding domain. They observed Tar oligomers consistent with a trimerof-dimers interpretation, but their crosslinking signal substantially depended on the presence of CheA and CheW and was significantly reduced on ligand binding.…”
Section: Detection Of Receptor Trimers Of Dimers In Vivomentioning
confidence: 99%